Rejection Sensitivity, Self-Compassion, and Aggressive Behavior: The Role of Borderline Features as a Mediator - Sommerfeld, Eliane; Shechory Bitton, Mally (Frontiers in Psychology, 2020)
This study used mediation analyses to examine the assumption that the presence of borderline personality features mediates the relationship between rejection sensitivity, self-compassion, and aggressive behavior. Sixty adults consisting of 31 participants diagnosed with borderline personality disorder and 29 participants with no diagnosis of borderline personality disorder were assessed for rejection sensitivity, self-compassion, aggressive behavior, and borderline personality features. Full mediation was found for the total aggression score, anger score, and hostility score regarding both self-compassion and rejection sensitivity. Full mediation was also found regarding rejection sensitivity and verbal and physical aggression. Partial mediation was found regarding self-compassion and verbal and physical aggression. These findings provide evidence that the presence of borderline personality features is an important factor in explaining the associations linking rejection sensitivity and self-compassion to aggressive behavior. High rejection sensitivity and low self-compassion are associated with greater borderline personality features, which in turn relate to increased aggressive behavior.